Indonesian language learning model based on critical and collaborative thinking in Law Study Program - Rahayu, Triwati; Suryadi, Suryadi (Universitas Ahmad Dahlan, 2025)
This study aims to develop a model for teaching Indonesian language based on critical and collaborative thinking in the Law Study Program. This research is classified as R&D development research. The development research model used is the R2D2 development model, which has three important stages, namely: (1) define focus, (2) design and development, and (3) disseminate. The subjects of this study were students who were taking Indonesian language courses in the Law Study Program, Faculty of Law, Ahmad Dahlan University Yogyakarta and Muhammadiyah University Purwokerto. The data analysis techniques used were descriptive qualitative and descriptive quantitative data analysis. The results of this study are as follows: (1) there is a need to develop a learning model that attracts students' interest in Indonesian language courses in the Law Study Program; (2) the model development has succeeded in developing a critical and collaborative thinking-based learning model for Indonesian language courses in the Law Study Program; (3) The pretest analysis results obtained a p-value of 0.855, which is known to be p-value > 0.05, so Ho is rejected. Thus, it can be concluded that the level of student thinking after treatment between the control and experimental groups was significantly different.